2021
DOI: 10.1016/j.jvs.2020.05.080
|View full text |Cite
|
Sign up to set email alerts
|

Burden and causes of readmissions following initial discharge after aortic syndromes

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Late rehospitalization following discharge in acute aortic syndrome is attributed to cardiovascular complications in about one-third of the patients. 17 , 18 Weiss et al . 18 have shown a two- to three-fold higher risk of non-aortic cardiovascular death, including the new occurrence of non-fatal cardiovascular event and heart failure in patients with aortic dissection, intramural haematoma, and penetrating aortic ulcer.…”
Section: Discussionmentioning
confidence: 99%
“…Late rehospitalization following discharge in acute aortic syndrome is attributed to cardiovascular complications in about one-third of the patients. 17 , 18 Weiss et al . 18 have shown a two- to three-fold higher risk of non-aortic cardiovascular death, including the new occurrence of non-fatal cardiovascular event and heart failure in patients with aortic dissection, intramural haematoma, and penetrating aortic ulcer.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have described AAD as one of the most catastrophic, life-threatening cardiovascular diseases with a typical chronobiological pattern, associated with extremely poor outcomes and a high risk of readmission (20)(21)(22)(23). AAD was described as a high incidence during the cold period, with a peak in January (22), suggesting a potential connection between climate characteristics and the onset of AAD.…”
Section: Discussionmentioning
confidence: 99%
“…For patients who underwent open or endovascular treatment for TBAD, we found that the risk of readmission within the first year was high, with rates of 40% for both groups by 300 days. Previously, in a small (n = 117) county-wide study, D'Oria and colleagues 24 assessed the long-term readmission rates for patients with various aortic syndromes (aortic dissection, intramural hematoma, and penetrating aortic ulcer) and found the cumulative incidence of readmission to be 45% at 2 years and 69% at 10 years. Furthermore, the authors found aortic and cardiovascular causes to be the most common reason for readmission during the early and late follow-up periods, respectively, which is consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%